IMPROVING STUDENT LEARNING OUTCOMES WITH GUIDED DISCOVERY METHOD USING GEOGEBRA SOFTWARE - Sulaiman, Sulaiman (Journal of the Indonesian Mathematics Education Society, 2019)
ABSTRACT Along with developing of science and technology, the education world should be willing to hold positive innovations for education advancement. Educational technology could change the conventional instruction into non-conventional. Therefore author wants to provide an alternative method of instruction that is able to make students more active, namely guided discovery methods using GeoGebra software.The purpose of this study was to determine student activities, student responses and improvement in student learning outcomes through the application of guided discovery methods using GeoGebra software with congruence topics of grade 9 of SMPN 1 Saronggi Sumenep academic year 2018/2019.This research was conducted in Sumenep on September 2, 2018 up to September 13, 2018 in semester I of the 2018/2019 academic year with a total of 22 students. This classroom action research was carried out for two cycles with each cycle through the stages of planning, implementation, observation, and reflection. Researchers used the observation method to determine student activities, questionnaires to determine student responses and and test methods to determine improvement in student learning outcomes. Data analysis uses descriptive data analysis.From the results of data analysis, it can be concluded that student activity has increased by 0.4 in the good category, student response has increased by 7.14%. with a very good category and student learning outcomes have increased by 11.91 with good criteria. So that the application of guided discovery methods using GeoGebra software can be said to be good to apply.Keywords: Guided discovery, GeoGebran software